Relevance of Chinese Goose (Anser cygnoides) in Experimental Epidemiology of Newcastle Disease - Campioni, Josie M.; Martins, Gislaine R. V.; Schmidt, Elizabeth M. S.; Paulillo, Antonio C.; Carrasco, Adriano O. T.; Testi, Alan J. P. (Brazilian Journal of Veterinary Pathology, 2012)
This study aimed to characterize the true epidemiological role played by the Chinese goose (Anser cygnoides) as a potential source of infection by the Newcastle disease virus (NDV). For this, Specific-Pathogen-Free chicks (SPF) were used and were housed with Chinese geese that had been inoculated with a pathogenic strain (velogenic viscerotropic, strain São João do Meriti) of NDV (DIE50=108.15/0.1 mL) pathogenic to chickens, by the ocular-nasal route. Each group was composed of 6 SPF Leghorn chicks and 3 geese. At 6 days (Group I) and 14 days (Group II) after inoculation of the Chinese geese with NDV, SPF chicks were put into direct contact with each goose group. Cloacal swabs were collected from both species (Chinese geese and SPF chicks) 6, 10 and 20 days after challenge to genome viral excretion by Reverse Transcription Polymerase Chain Reaction (RT-PCR). Chinese geese did not demonstrate any clinical signs of Newcastle disease (ND). They were refractory to the clinical disease with the NDV. However, NDV genome was detected 20 days after challenge. Therefore, NDV carrier status was demonstrated by Chinese geese. Moreover, 100% of SPF chicks housed with the infected Chinese geese had died by 6 (Group I) and 14 days (Group II) after challenge. Thus, the transmission of the pathogenic virus from the Chinese geese to cohabiting SPF chicks was evident within 20 days of the experimental infection. This reveals the epidemiological importance of Chinese geese as a potential transmitter of NDV infection to other commercial birds that could be raised in close proximity.